Enhancing Rice Productivity in the Unfavourable Ecosystems of Bangladesh (Bangladesh Rice Journal, 2021)
Rice is cultivated in the three seasons (Aus, Aman, and Boro) across four ecotypes, including irrigat-ed, rainfed upland, rainfed lowland, and deep water in Bangladesh. Rice farming in unfavourable ecosystems is highly exposed to abiotic stresses and extreme weather events (floods, droughts, storm surges, and cyclones), and its performance is frequently affected by the multiple-stresses and extreme weather events. Besides, the increasing demand for rice for the growing population and decreasing scarce resources, including arable land and fresh-water for irrigation aggravated the concern about sustainable rice production systems under future conditions. Thus, the paper aimed to exploit unfa-vourable ecosystems to increase total rice production for meeting future demand. Secondary data were analyzed to achieve the objectives of the study. BR23, BRRI dhan40, BRRI dhan41, BRRI dhan47, BRRI dhan53, BRRI dhan54, BRRI dhan61, BRRI dhan67, BRRI dhan73, BRRI dhan97, BRRI dhan99, BINA dhan-8 and BINA dhan-10 are resilient to salinity. Besides, BRRI dhan56, BRRI dhan57, BRRI dhan66, BRRI dhan71, and BRRI dhan83 are resilient to drought, and BRRI dhan51, BRRI dhan52, BRRI dhan79, BINA dhan11, and BINA dhan-12 are tolerant to submergence. The BR18, BRRI dhan36, BRRI dhan67, and BRRI dhan69 are some-extent resilient to cold. The research has been con-tinuing for developing further stress-tolerant higher yield potential rice cultivars for unfavourable ecosystems. The increased adoption of currently available stress-tolerant rice cultivars has the poten-tial to give a substantially higher yield than that of locally popular rice cultivars in the unfavourable ecosystems. Therefore, the dissemination of stress-tolerant cultivars to 75% of total rice cropping are-as of saline (0.37 Mha), submergence (1.08 Mha), and drought (2.94 Mha) ecosystem may contribute to increasing rice production in the ecosystems by 1.26 MT, 3.45 MT, and 9.18 MT, respectively. Re-sulting from that 13.89 MT rice will be added to the national rice basket in 2050. The policy supports are needed to strengthen for developing and rapid dissemination of the stress-tolerant cultivars in the unfavourable ecosystems for meeting the increased demand of rice of the growing population under future conditions.Bangladesh Rice J. 24 (2): 83-102, 2021